Polyurethane–zinc borate composites with high oxidative stability and flame retardancy - Yıldız, Basar; Seydibeyoğlu, M. Özgür; Güner, F. Seniha (Elsevier BV, 2009)
Novel polyurethane zinc borate composites were prepared with the main aim to increase the flame retardancy of the polyurethane. It was discovered that the zinc borate had very significant effects on the oxidative stability of the neat polymer which was first observed by oxygen induction time tests and supported with actual weathering chamber tests. The oxidative stability of zinc borate-filled polyurethane was compared with the polyurethane stabilized with a commercial light stabilizer, Tinuvin B75 from Ciba SC. The performance of zinc borate-filled polyurethane was much better, as shown by oxygen induction time and weathering chamber tests. Additionally the flame retardancy was measured and significant flame retardancy was achieved. Mechanical tests, thermogravimetric analysis and scanning electron microscope studies were performed to characterize the products.